PENERAPAN MEDIA PEMBELAJARAN PAPAN SAKU JURANG UNTUK MENINGKATKAN HASIL BELAJAR MATERI OPERASI HITUNGAN BILANGAN CACAH - Sindy Damayanti; Budiyono; Khoirul Fansuri; Agus Sumarliani; Dewi Astutik Eka Nurcahyo Sardji Wahyuliarti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research was to determining the application of the abyss pocket board learning media in improving learning outcomes in whole number counting operation material in class IV at SDN Gading VII Surabaya. The research method used is Classroom Action Research (CAR) with two cycles, where each cycle consists of planning, action, observation and reflection. There are 28 students in class IV-A with a focus on improving understanding of addition and subtraction of whole numbers. Data is collected through observation, tests and documentation. The results of data showed a significant increase in student learning outcomes after implementing the gap pocket board media. In the pre-cycle, only 39% of students achieved a minimum completion score (KKM) of 75, while in cycle I it increased to 68% and in cycle II to 89%. This research reveals that the use of pocket board media is effective in improving mathematics learning outcomes by creating a more interactive and enjoyable learning atmosphere. Therefore, this media can be recommended as an aid in learning mathematics, especially for adding and subtracting whole numbers.